Strategic Management Implementation in Teacher and Educational Personnel Management to Improve Education Quality at MAN Kota Cimahi - Rahmatullah, Irfan; Nugraha, Mulyawan Safwandy (Journal of Education and Teaching Learning, 2024)
This research is intended to find out about the implementation of strategic management of the management of teachers and education personnel in improving the quality of education at MAN Kota Cimahi. This research uses a qualitative approach to find out or describe the real and facts in the field. The method used is descriptive of the phenomenon of what is observed from a meaning, interconnected and based on existing reality. The types of data used are primary and secondary. The data collection techniques used include direct observation at the research location, interviews and documentation. Data analysis techniques use data reduction techniques, compilation of units, interpretation and conclusion drawing. This research focuses on strategic management in improving the management of teachers and education personnel at MAN Kota Cimahi. Education is one very important aspect, the management of teachers and education personnel are two main determining factors in the continuity of the teaching and learning process. The challenge of education management is now experiencing several problems such as the low quality of teachers and education personnel, lack of facilities and infrastructure, and lack of motivation and professionalism of teachers. The results of the study indicate that the implementation of strategic management in the management of teachers and education personnel at MAN Kota Cimahi is needed so that planning, organizing, implementing and evaluating can run accordingly so that the objectives of the management of teachers and education personnel run well and have a positive impact on improving performance, management of teachers and education personnel, as well as improving the vision and mission and quality of education quality.